Cohort profile: Health in Central Denmark (HICD) cohort - a register-based questionnaire survey on diabetes and related complications in the Central Denmark Region. Issue 7 (7th July 2022) - Bjerg, Lasse; Dalsgaard, Else-Marie; Norman, Kasper; Isaksen, Anders Aasted; Sandbæk, Annelli
Abstract : Purpose: The Health in Central Denmark (HICD) cohort is a newly established cohort built on extensive questionnaire data linked with laboratory data and Danish national health and administrative registries. The aim is to establish an extensive resource for (1) gaining knowledge on patient-related topics and experiences that are not measured objectively at clinical health examinations and (2) long-term follow-up studies of inequality in diabetes and diabetes-related complications. Participants: A total of 1.3 million inhabitants reside in the Central Denmark Region. Using register data and a prespecified diabetes classification algorithm, we identified 45 507 persons aged 18–75 years with prevalent diabetes on 31 December 2018 and a group without diabetes of equal size matched by sex, age and municipality. A 90-item questionnaire was distributed to eligible members of this cohort on 18 November 2020 (estimated time required for completion: 15–20 min). Findings to date: We invited 90 854 persons to take part in the survey, of whom 51 854 answered the questionnaire (57.1%). Among these respondents, 2, 832 persons had type 1 diabetes (55.9%), 21, 140 persons had type 2 diabetes (53.2%), while 27, 892 persons were part of the matched group without diabetes (60.4%). In addition to questionnaire data, the cohort is linked to nationwide registries that provide extensive data on hospital diagnoses and procedures, medication use and socioeconomic status decades before enrolment while laboratory registries has provided repeated measures of biochemical markers, for example, lipids, albuminuria and glycated haemoglobin up to 10 years before enrolment. Future plans: The HICD will serve as an extensive resource for studies on patient-related information and inequality in type 1 diabetes and type 2 diabetes. Follow-up is planned to continue for at least 10 years and detailed follow-up questionnaires, including new topics, are planned to be distributed during this period, while registry data are planned to be updated every second year.